ARTHROSCOPIC SHOULDER STABILIZATION IN HIGH SCHOOL FOOTBALL PLAYERS: RECURRENT INSTABILITY WITH RETURN TO CONTACT SPORT. Issue 4 (28th April 2020) - Stambaugh, Jessica; Edmonds, Eric; Pennock, Andrew
Background: The etiology of recurrent shoulder instability after arthroscopic surgery in the high school American football population remains unknown. Purpose/Hypothesis: To determine the risk of recurrent instability after shoulder arthroscopy upon return to competitive football. The hypothesis was that the rate of recurrence would be greater in high school players with more years of eligibility remaining (YER), suggesting greater likelihood of return to football after surgery. Methods: Consecutive male high school football players with at least one year of eligibility remaining who sustained traumatic in-season shoulder instability episode(s) and underwent arthroscopic labral stabilization by two Orthopaedic Sports surgeons at Rady Children's Hospital San Diego between 2012 and 2017 were identified. 64 subjects aged 14-17 met inclusion criteria of which 45 were able to be contacted and included in analyses. Average follow up period was 4.06 years. Patients and/or families were contacted by phone to discuss (1) recurrent instability episodes and (2) return to competitive sport and/or recreational athletic activity. Statistics were conducted using chi square analysis to compare recurrence of instability with return to sport. Results: Surgery itself was career ending in 50% of cases due to reported fear of recurrent football-related injury. The hypothesis that career longevity in terms of years of eligibility remaining (YER) affects return to game play in this young active population remains unclear although preliminary results suggest positive exponential correlation. Comparative analysis demonstrates a statistically significant difference between rate of recurrence in high school football players that return to contact sports vs transition to non-contact activity after arthroscopic shoulder stabilization. Interestingly, football players who concurrently played baseball during high school demonstrated decreased risk of postoperative instability episodes. Conclusion: Risk of recurrent instability after shoulder arthroscopy is increased in high school football players who return to competitive contact sports whereas transition to non-contact and/or recreational activity likely confers protective effect. High school football players who play baseball may derive functional benefit from cross training. : Figure. Proportion of recurrent shoulder instability after arthroscopic stabilization in high school football players stratified by years of eligibility remaining (YER) demonstrating positive exponential correlation relationship.